Strategi Komunikasi PT.Pos Indonesia Dalam Meningkatkan Reputasi Perusahaan - Rosanti Utami Dewi S.Y; Sayida Meisani; Leadya Raturahmi (LPPM Universitas ARS, 2021)
This research was motivated by competition in the logistics business in suburban areas where each company provides competitive services and various attractive promotions. This study aims to identify and explain how Public Relations Communication Strategies in Improving Company Image at PT. Pos Indonesia in Garut Regency. This study uses a descriptive qualitative approach using observation data collection techniques, and interviews, and documentation studies. The main informants in this study were four company internal officers at PT. Pos Indonesia In Garut Regency selected using a purposive sampling technique. This study uses a public relations strategy step model, namely; situation analysis, planning and program strategy, action and communication, and evaluation. The results showed that the communication strategy of Public Relations in improving the company image at PT. Pos Indonesia in Garut Regency through internal communication and external communication. Situation analysis is carried out, by determining the target. Strategy planning and programming are carried out by compiling programs, objectives, actions, and even strategies and tactics. Implementation is carried out by utilizing publications including brochures, sponsors, CSR, PKBL, and social media. Evaluation is carried out, namely within the period after the program is implemented.